Construction of Quaternary Stereocenters by Palladium‐Catalyzed Carbopalladation‐Initiated Cascade Reactions - Ping, Yuanyuan; Li, Yuxiu; Zhu, Jieping; Kong, Wangqing (Angewandte Chemie International Edition, 2019)
The enantioselective synthesis of molecules containing quaternary stereocenters is a field of intense research interest and development. Among the known organic transformations, carbopalladation‐initiated domino transformations constitutes a general method for the construction of compounds containing cyclic or spiro quaternary stereocenters. In this Minireview, recent achievements in palladium‐catalyzed domino Heck/C−H functionalizations and developments in enantioselective carbopalladation‐initiated domino processes are summarized. Domino effect: Recent advances in palladium‐catalyzed domino reactions initiated by intramolecular carbopalladation are summarized. Particular emphasis is given to C−H functionalization by transient σ‐alkylpalladium species and enantioselective domino Heck cyclization/nucleophilic trapping cascades.